The effects of CLIL on mathematical content learning: A longitudinal study - Surmont, Jill; Struys, Esli; Van Den Noort, Maurits; Van De Craen, Piet (Studies in Second Language Learning and Teaching, 2016)
Previous research has shown that content and language integrated learning (CLIL), an educational approach that offers content courses through more than one educational language, increases metalinguistic awareness. This improved insight into language structures is supposed to extend beyond the linguistic domain. In the present study, the question whether pupils who learn in a CLIL environment outperform their traditionally schooled peers in mathematics is investigated. In total, 107 pupils entered the study. All participants were in the first year of secondary education at a school in Ostend, in Flanders, the Dutch-speaking part of Belgium. Thirty-five pupils followed CLIL education in a foreign language (French) and 72 followed traditional education that was given in the native language (Dutch). All participants were tested using a mathematical test at the beginning of the year, after three months, and after ten months. The first measurement of the mathematical scores showed that the two groups did not differ. In accordance with our hypothesis, the CLIL group scored higher than the non-CLIL group after ten months. Surprisingly, an effect was also found after three months. To conclude, CLIL appears to have a positive impact on the mathematical performance of pupils even after a short period of time.